Terapia gênica de isquemia de membro de camundongo com os genes Gm-Csf e M-Csf - Mansano, Barbara Sampaio Dias Martins [UNIFESP] (2017)
Cancer is the world's largest public health problem and the second leading cause of death in the United States. It is a disease associated with aging. Infections are a serious cause of morbidity and mortality in cancer patients, especially infections related to health care. The platelets play several important functions in homeostasis that go beyond their role in coagulation and thrombosis, to the immune system already described in cancer and infection, interrelated with co-stimulatory molecules of the immune response, such as OX40 and CD40L, and by adhesion to other cell groups forming the platelet aggregates (AGP).Understanding these molecules in this group of patients may help in clinical management. The objective of the study was to analyze the circulating platelet aggregate profile and the prevalence of OX40 and CD40L in elderly cancer patients with acute bacterial infection. A cross - sectional and translational study was performed with 91 (45 patients with infection - CI and 46 patients without infection - SI) and 45 controls. Serum levels sCD40L was performed by enzyme immunosorbent assay (ELISA). The determination of platelets (CD41a +), AGP / CD62P +, AGP / CD40L+ and OX40 on the cell surface was performed by flow cytometry. Mann-Whitney and Kruskal-Wallis tests were used for analysis of medians between two and three groups, respectively. Values of p <0.05 were considered significant. For statistical analysis, GraphPadPrism v6.0 was used. Elevated basal levels of CD3 + /OX40 + T lymphocytes werw higher in patients (p <0.0001) when compared to controls. Patients with infection had reduced percentage levels of monocytes / OX40 + and neutrophils / OX40 + (p <0.0001, p = 0.01 respectively). Lymphocyte / CD40L + and platelet / CD40L + levels were higher during infection (p = 0.02, p = 0.0003, respectively). Elevated basal levels of AGP-lymphocytes, and reduced AGP-monocytes when compared to controls (p = 0.003, p = 0.04, respectively) were found. The levels of AGP-monocytes and AGPneutrophils were reduced in IC patients (p <0.004 and p = 0.009, respectively) and SI (p =0.001 and p = 0.01, respectively) when compared to controls, and similar between CI groups and SI. (P = 0.03). Levels of AGP-lymphocytes (p= 0,03), AGP-monocytes (p = 0.04), and AGP-neutrophils (p = 0.009) in the paired analysis before (baseline) and during infection were higher in baseline when compared to levels during infection. Levels of platelets /CD62P +, AGP-monocytes / CD62P + and AGP-neutrophils / CD62P + in IC and SI patients were lower when compared to controls. In the analysis of AGP-neutrophils / CD62P +, IC patients presented decreased levels when compared to SI. In the paired analysis, IC patients had elevated baseline levels of activated platelets and AGP-lymphocytes / CD62P + when compared to levels during infection (p <0.0001 and p = 0.02, respectively). Baseline levels of AGP-lymphocytes / CD40L + and AGP-monocytes / CD40L + patients were reduced when compared to controls (p <0.0001). Percentage levels of AGP-lymphocytes / CD40L + were reduced in patients during infection compared to controls (p <0.03). CI patients had elevated levels of AGP-neutrophils / CD40L + when compared to SI (p = 0.006) and similar to controls. SI patients presented reduced levels of this population when compared to controls (p <0.0001). In the analysis of sCD40L, there was no statistical difference between the groups. Changes in the expression of OX40 +, CD40L + and platelet aggregates may be associated with regulation of the immune response to infections in elderly cancer patients, as well as correlations with tumor microenvironment and immunosenescence secondary to carcinogenesis and cytoreductive treatments. All this may explain, in part, the frequency and presentation of severe infectious conditions in the elderly with cancer.